Development and characterization of novel highly-loaded itraconazole poly(butyl cyanoacrylate) polymeric nanoparticles - Ćurić, Anamarija; Möschwitzer, Jan; Fricker, Gert (European journal of pharmaceutics and biopharmaceutics, 2017)
Treatment of cryptococcal meningitis with antifungals such as itraconazol is difficult due their low concentration in the brain. Therefore, drug carriers with high payload are highly desired. But, generation of itraconazole loaded poly(butyl cyanoacrylate) nanoparticles with higher drug load, for instance more than 20% drug, is challenging. In present study we were able to generate novel highly loaded itraconazole poly(butyl cyanoacrylate) nanocapsules containing up to 99% (w/w) itraconazole and 1% polymer (w/w). Moreover, a controllable manufacturing procedure using a one-step emulsion solvent evaporation technique was established in order to discriminate between itraconazole loaded nanocapsules and nanospheres. Furthermore, it could be demonstrated that our novel nanocapsules can be decorated with targeting molecules such as apolipoprotein E. More precisely, apolipoprotein E was covalently bound to a maleimide linker, which was integrated within the surface of polymeric nanoparticle. This covalent binding of apolipoproteinE to the surface of a drug delivery system enables targeting of low density lipoprotein receptor (LDLR) expressed on endothelial brain capillary cell membranes, making our novel highly loaded itraconazole poly(butyl cyanoacrylate) nanocapsules a promising drug delivery system for treatment of cryptococcal meningitis.